INaturalist is useful at enhancing biodiversity studies as evident from southern African freshwater crabs (Decapoda: Brachyura: Potamonautidae). Issue 3 (30th August 2022) - Daniels, Savel R; Barnes, Aaron; Peer, Nasreen; Egan, Vincent T; Taylor, Ricky; Taylor, Robert W; van der Colff, Dewidine
Abstract: The value of the citizen science platform iNaturalist was explored using photographic observations of southern African freshwater crabs (Potamonautidae Bott, 1970, among two genera Potamonautes sensu stricto MacLeay, 1838 and Martimonautes Cumberlidge & Daniels, 2022 ) in combination with specimen data deposited in the South African Museum (Iziko Museums of Cape Town, South Africa). Species identification of photographic observations were assessed, and the identification of taxa corrected where necessary. From these records, the habitat type and distribution of the species were noted. The area of occupancy (AOO) and the extent of occurrence (EOO) were calculated where range extensions for species were observed. The results demonstrate that riverine/mountain stream freshwater crabs are over-represented in their frequency but species occurring in swamps/forests were under-represented. Using iNaturalist spatial data for South Africa we can identify several unsampled gaps in the country which included the Free State and North West, Gauteng and the Northern Cape, followed by Limpopo, Mpumalanga, and the Eastern Cape provinces. The Western Cape and KwaZulu-Natal had the highest number of freshwater crab records on iNaturalist. The remaining southern African countries, Angola, Botswana, Eswatini, Lesotho, Malawi, Mozambique, Namibia, and Zimbabwe, have few iNaturalist records. Range extensions were observed in four South African species based on iNaturalist records ( P. clarus Gouws, Stewart & Coke, 2000, P. flavusjo Daniels, Phiri, & Bayliss, 2014, P. isimangaliso Peer & Gouws, 2015, and P. mariepskoppie Daniels, Barnes, Marais & Gouws, 2021 ) with increases in AOO and EOO. We also observed a new undescribed freshwater crab on iNaturalist and corroborated this observation by sequencing these specimens for the cytochrome oxidase one subunit (COI) locus. Photographic quality is critical for taxonomic inference. Citizen science platforms such as iNaturalist can be invaluable for the discovery and documentation of biodiversity and provide new spatial data for species distributions that in turn can aid conservation tools.